2013
DOI: 10.1002/pssa.201228793
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of X‐ray irradiated CdSe nanocrystals embedded in dielectric matrices

Abstract: The effect of X‐ray irradiation (up to 3200 Gy) on the photoluminescence (PL) of CdSe nanocrystals embedded in polyacrylamide and borosilicate glass matrices is studied. In both cases no PL quenching is observed: for the polyacrylamide‐embedded CdSe nanocrystals the PL intensity remains stable, while for the borosilicate glass‐embedded nanocrystals it increases somewhat. The obtained PL behavior correlates well with the optical absorption data. This testifies to the radiation stability of the optical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…and . Similarly to CdSe and Se‐rich CdS 1− x Se x nanocrystals, two bands are clearly revealed in the PL spectra. A relatively narrow (near 0.1 eV) higher‐energy PL maximum is located slightly below the first absorption peak energy corresponding to the transition between 1s e electron and 1S 3/2 hole states (HOMO–LUMO transition) in the nanocrystals.…”
Section: Resultsmentioning
confidence: 97%
“…and . Similarly to CdSe and Se‐rich CdS 1− x Se x nanocrystals, two bands are clearly revealed in the PL spectra. A relatively narrow (near 0.1 eV) higher‐energy PL maximum is located slightly below the first absorption peak energy corresponding to the transition between 1s e electron and 1S 3/2 hole states (HOMO–LUMO transition) in the nanocrystals.…”
Section: Resultsmentioning
confidence: 97%
“…1 demonstrate that the PL of CdSe-QDs is almost completely quenched already after $18 kGy (SiO 2 ). Although previous works on matrix-embedded CdSe-NCs showed that these are resistant up to 3.2 kGy, 29 experiments using higher doses have not been reported for these QDs yet. Consequently, the absorption of X-rays in this material system generates additional non-radiative channels in the QDs, and the resulting effect on luminescence increases with the absorbed dose.…”
mentioning
confidence: 88%
“…2, top, inset), in accordance with previous ensemble studies. 28,29 Instead, a significant drop in PL intensity occurs for higher doses, as observed in CdTe/CdS-QDs. 31 A control nonirradiated sample of CdSe-QDs shows no significant change of PL intensity over time (Fig.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, the results suggest that the damages induced by X‐rays do not affect the recombination mechanism responsible for the light emission of Si‐NCs. Moreover, in terms of radiation hardness, they seem to perform fairly well, also when compared with Cd‐based alternatives, which are usually exposed to lower doses (<4 kGy) and exhibit strong quenching already at those values .…”
Section: Resultsmentioning
confidence: 92%